(untitled) (Raparin Journal of Humanities (RJH), 2025)
Satire as an important aspect of literature is about mocking and criticizing the follies of the society and people through a literary genre. Social satire, as the subject of this research, is a witty criticism based on the flaws of the society; its goal is to drive social change. Social satire was an essential part of the southern Kurdistan journalism during the (1920-1950). Poets, writers at the period used it to criticize the vices of the Kurdish society for changing and developing their society. The present research is entitled (Social Satire in the Southern Kurdistan Journalism 1920-1950). It is composed of two chapters. The first chapter, in two sections, discusses the concept of satire, its definition, and the history of Kurdish journalism. The second chapter is divided into two sections as well. The first section discusses satire and its types in terms of content. The second section is devoted to the social satire in the southern Kurdistan journalism 1920-1950. The research ends with the results and the list of the references consulted for the study.